KIAT mengelola masjid dan mushalla di cabang dan ranting Muhammadiyah / Mutiullah...[et.al]; penyunting, Muhammad Hamdi, M. Jamaluddin Ahmad - MUTIULLAH; MUHAMMAD HAMDI; JAMALUDDIN AHMAD, M. (Suara Muhammadiyah, 2017)
x, 75 halaman ; 15 cm.